Taxonomic notes on the genus Septoria of several ornamental plants in Iran - H. Azimi-Motem; L. L. Osipyan (ՀՀ ԳԱԱ հրատ.)
Collections of ornamental plants (Antirrhinum majus L., Cercis siliquastrum L., Chrysanthemum sp., Cornus sanguinea L., Digitalis sp., Gladiolus sp., Hedera helix L., Rosa sp.) with leaf spot symptoms, and pycnidia signs from Mycological Collection of the Iranian Research Institute of Plant Protection, and new collections, collected from north of Iran (Caspian sea area), were studied to investigate the causal organisms. Studied materials belong to eight host species. Studies revealed that Septoria antirrhini Desm., S. cercidis Fr., S. chrysanthemella Sacc., S. cornicola Desm., S. digitalidis Pass., S. gladioli Pass., S. hederae Desm., S. rosae Desm. respectively are the causal organisms on studied host plants. All collections are preserved in the Mycological Collection of the Iranian Research Institute of Plant Protection. The descriptions of Iranian samples of these species are given for the first time. One species (S. rosae Desm.) is new for Iranian mycoflora. Ուսումնասիրված է բծավորության ախտանշաններով և պիկնիդիալ սպորատվության հատկանիշներով 8 տեսակ դեկորատիվ բույս (Antirrhinum majus L., Cercis siliquastrum L., Chrysanthemum sp., Cornus sanguinea L., Digitalis sp., Gladiolus sp., Hedera helix L., Rosa sp.) Իրանի Բույսերի Պաշտպանության Գիտահետազոտական Ինստիտուտի Սնկաբանական Հավաքածուից, ինչպես նաև այդ բույսերի նոր հավաքածուներ Իրանի հյուսիսից (Կասպից ծովի շրջան): Հետազոտված է պիկնիդիալ սպորատվության կառուցվածքը: Որոշված է 8 սեպտորիոզի հարուցիչ (Septoria antirrhini Desm., S. cercidis Fr., S. chrysanthemella Sacc., S. cornicola Desm., S. digitalidis Pass., S. gladioli Pass., S. hederae Desm., S. rosae Desm.): Առաջին անգամ տրված են նկարագրություններ այս տեսակների Իրանի նմուշների համար: Տեսակներից մեկը` S. rosae Desm., նոր է Իրանի համար: majus L., Cercis siliquastrum L., Chrysanthemum sp., Cornus sanguinea L., Digitalis sp., Gladiolus sp., Hedera helix L., Rosa sp.) из Микологической Коллекции Иранского Научно-исследовательского Института Защиты Растений, а также новые образцы этих растений, собранные на севере Ирана (область Каспийского моря) с симптомами пятнистости и признаками пикнидиального спороношения. Исследовано строение пикнидиального спороношения. Идентифицировано 8 видов возбудителей септориоза (S. antirrhini Desm., S. cercidis Fr., S. chrysanthemella Sacc., S. cornicola Desm., S. digitalidis Pass., S. gladioli Pass., S. hederae Desm., S. rosae Desm.). Впервые даны описания иранских образцов этих видов. Один из видов (S. rosae Desm.) является новым для Ирана.
Keywords: Biology; Biological Diversity